Insufficient Energy From MgO Exsolution to Power Early Geodynamo. Issue 22 (27th November 2017) - Du, Zhixue; Jackson, Colin; Bennett, Neil; Driscoll, Peter; Deng, Jie; Lee, Kanani K. M.; Greenberg, Eran; Prakapenka, Vitali B.; Fei, Yingwei
Abstract: The origin of Earth's ancient magnetic field is an outstanding problem. It has recently been proposed that exsolution of MgO from the core may provide sufficient energy to drive an early geodynamo. Here we present new experiments on Mg partitioning between iron‐rich liquids and silicate/oxide melts. Our results indicate that Mg partitioning depends strongly on the oxygen content in the iron‐rich liquid, in contrast to previous findings that it depends only on temperature. Consequently, MgO exsolution during core cooling is drastically reduced and insufficient to drive an early geodynamo alone. Using the new experimental data, our thermal model predicts inner core nucleation at ~850 Ma and a nearly constant paleointensity. Key Points: Experimentally determined Mg partitioning between iron‐rich liquid and silicate melt Mg partitioning depends strongly on the oxygen content in iron‐rich liquid MgO exsolution during core cooling is drastically reduced and insufficient to drive an early geodynamo alone